Mast Cells May Differentially Regulate Growth of Lymphoid Neoplasms by Opposite Modulation of Histamine Receptors - Paudel, Sandeep; Mehtani, Deeksha; Puri, Niti (Frontiers in Oncology, 2019)
Cancer microenvironment is complex and consists of various immune cells. There is evidence for mast cell (MC) infiltration of tumors, but their role thereof is poorly understood. In this study, we explored the effects of mast cell and their mediators on the growth of hematological cancer cells. The affect is demonstrated using RBL-2H3 MCs, and YAC-1, EL4 and L1210 as hematological cancer cell lines. Direct contact with MCs or stimulation by their mediators caused growth inhibition of YAC-1 cells, growth enhancement of EL4 cells and no change in growth of L1210 cells. This effect was confirmed by cancer cell recovery, cell viability, mitochondrial health and cell cycle analysis. MCs showed mediator release in direct contact with tumor cells. MC mediators’ treatment to YAC-1 and EL4 yielded exactly opposite modulations of survival markers, Survivin and COX-2 and apoptosis markers, Caspase-3, Bcl-2, in the two cell lines. Histamine being an important MC mediator, effect of histamine on cell recovery, survival markers and expression of various histamine receptors and their modulation in cancer cells was studied. Again, YAC-1 and EL4 cells showed contrary histamine receptor expression modulation in response to MC mediators. Histamine receptor antagonist co-treatment with MC mediators to the cancer cells suggested a major involvement of H2 and H4 receptor in growth inhibition in YAC-1 cells, and contribution of H1, H2 and H4 receptors in cell growth enhancement in EL4 cells. L1210 showed changes in the histamine receptors’ expression but no effect on treatment with receptor antagonists. It can be concluded that anti-cancerous action of MCs or their mediators may include direct growth inhibition, but their role may differ depending on the tumor.